Legal Uncertainty for Police Members in the Limits of Positions Outside the Police - Anwar Sunarjo; Riswadi Riswadi (Riviera Publishing, 2024)
This research examines the legal uncertainties surrounding restrictions on police officers holding positions outside the police institution, focusing on the analysis of Law Number 2 of 2002 concerning the Indonesian National Police. Using a normative legal research method with legislative and conceptual approaches, the study reviews relevant legal provisions and principles of legal certainty and separation of powers. Key findings reveal significant regulatory ambiguities in defining permissible external roles, enforcement mechanisms, and conditions under which police officers may hold such positions. These gaps contribute to overlapping authorities, legal inconsistencies, and potential conflicts of interest. The study concludes by recommending specific policy revisions, including clarifying legal provisions, strengthening oversight mechanisms, and establishing clear criteria for permissible external roles. These measures aim to enhance legal certainty, maintain institutional integrity, and foster greater public trust in law enforcement.